2015
DOI: 10.1159/000375395
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Frequency-Associated Vestibular-Evoked Myogenic Potential Responses in Ménière's Disease

Abstract: Thirty subjects with unilateral Ménière's disease (MD) and 18 age-matched controls underwent cervical (cVEMP) and ocular vestibular-evoked myogenic potential (oVEMP) testing using bilateral air-conducted stimulation (ACS) with stimulus frequencies of 500 and 1,000 Hz. The aim of this study is to determine the diagnostic value of frequency-associated responses in MD using oVEMP and cVEMP following 500- and 1,000-Hz ACS. In healthy controls and unaffected ears, responses to 500 Hz were found better than 1,000-Hz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 21 publications
(29 reference statements)
4
17
0
Order By: Relevance
“…Our data suggest that patients with MD have a higher ratio than those presenting with non‐Meniere's vertigo, reflecting a tuning shift to a higher best stimulation frequency in MD. Our results are consistent with others . Sandhu et al consistently noted that MD patients had decreased cVEMP amplitude at 500 Hz when compared to healthy individuals and better responses at higher frequencies (ie, a tuning shift).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our data suggest that patients with MD have a higher ratio than those presenting with non‐Meniere's vertigo, reflecting a tuning shift to a higher best stimulation frequency in MD. Our results are consistent with others . Sandhu et al consistently noted that MD patients had decreased cVEMP amplitude at 500 Hz when compared to healthy individuals and better responses at higher frequencies (ie, a tuning shift).…”
Section: Discussionsupporting
confidence: 93%
“…Our study aimed to assess the value of cVEMP for the diagnosis of MD, particularly the 1,000/500 Hz amplitude ratio. It has been reported that in healthy individuals, the stimulating frequencies that resulted in the highest amplitude responses are found at 250–500 Hz, and that in healthy individuals the cVEMP 1,000/500 Hz amplitude ratio should be <1 . Our data suggest that patients with MD have a higher ratio than those presenting with non‐Meniere's vertigo, reflecting a tuning shift to a higher best stimulation frequency in MD.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Because background muscle activities could interfere with the VEMP amplitudes, the interpeak amplitudes were normalized [2,25] . The asymmetry ratio was calculated for comparison between the right and left ears, using the formula described by Murofushi et al [22] .…”
Section: Stimulus Design and Recording Setupmentioning
confidence: 99%